Mitochondrial Dysfunctions in Type I Endometrial Carcinoma: Exploring Their Role in Oncogenesis and Tumor Progression - Clara Musicco (International Journal of Molecular Sciences, 2018)
Type I endometrial cancer (EC) is the most common form of EC, displaying less aggressive behavior than type II. The development of type I endometrial cancer is considered a multistep process, with slow progression from normal endometrium to hyperplasia, the premalignant form, and endometrial cancer as a result of an unopposed estrogenic stimulation. The role of mitochondria in type I EC tumor progression and prognosis is currently emerging. This review aims to explore mitochondrial alterations in this cancer and in endometrial hyperplasia focusing on mitochondrial DNA mutations, respiratory complex I deficiency, and the activation of mitochondrial quality control systems. A deeper understanding of altered mitochondrial pathways in type I EC could provide novel opportunities to discover new diagnostic and prognostic markers as well as potential therapeutic targets.